Pengaruh Profitabiitas Struktur Aktiva Dan Ukuran Perusahaan Terhadap Struktur Modal (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2020-2022) - Handayani, Putri; Suriyanti, Linda Hetri; Fitriana, Nur (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The aim of this research is to analyze the influence of profitability, asset structure and company size on capital structure. This research is a case study of a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. For this research, the data source used is secondary data obtained from IDX (Indonesian Stock Exchanges) in the form of annual reports of food and beverage sector companies listed on the Indonesian Stock Exchange (BEI), namely (www.idx.co.id). The data analysis technique used in this research is descriptive analysis and research hypothesis testing which is carried out using a multiple regression model. The results of the analysis conclude that profitability, asset structure and company size influence capital structure. This research uses 3 independent variables and 1 dependent variable, namely profitability, asset structure and company size on capital structure where it can be seen that the Adjusted R Squared value is 57.8% which has an influence in this research so that there is still a remaining 42.2% which is influenced by other variables outside this research.